Alteration of somatosensory response in adulthood by early life stress - Takatsuru, Yusuke; Koibuchi, Noriyuki (Frontiers in Molecular Neuroscience, 2015)
Early-life stress is well known as a critical risk factor for mental and cognitive disorders in adulthood. Such disorders are accompanied by altered neuro- (synapto-) genesis and gene expression. Because psychosomatic disorders induced by early-life stress (e.g., physical and/or sexual abuse, and neglect) have become a socio-economic problem, it is very important to clarify the mechanisms underlying these changes. However, despite of intensive clinical and animal studies, such mechanisms have not yet been clarified. Although the disturbance of glucocorticoid and glutamate homeostasis by stress has been well documented, it has not yet been clarified whether such disturbance by early-life stress persists for life. Furthermore, since previous studies have focused on the detection of changes in specific brain regions, such as the hippocampus and prefrontal cortex, it has not been clarified whether early-life stress induced changes in the sensory/motor system. Thus, in this review, we introduce recent studies on functional/structural changes in the somatosensory cortex induced by early-life stress. We believe that this review provides new insights into the functional alteration of the somatosensory system induced by early-life stress. Such information may have clinical relevance in terms of providing effective therapeutic interventions to early-life-stressed individuals.